2019
DOI: 10.1590/0001-3765201920180991
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of Lonchocarpus araripensis lectin in rat acute models of inflammation

Abstract: Dalbergieae tribe lectins, possessing binding affinity for galactose and mannose, present inflammatory and nociceptive effects, while those for N-acetylglucosamine are anti-inflammatory. Since the anti-inflammatory effect of the seed lectin of L. araripensis (LAL) had been already demonstrated in mice, this effect was presently evaluated in rat models of acute inflammation. LAL (0.01-1 mg/kg) was administered by intravenous (i.v.) route in male Wistar rats 30 min before paw edema induction by dextran or carrag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…The differential leukocyte count showed that neutrophils are the principal target cells involved in the anti-in ammatory effect of AAL. Similar results have been observed in rats for the lectins isolated (Dalbergieae tribe) from Lonchocarpus sericeus [17,18] and L. araripensis [19], presenting binding a nity for N-acetylglucosamine. In addition, the interference of AAL in neutrophil migration was also con rmed by the reduced MPO activity in the paw, a heme-containing enzyme that is abundantly expressed in neutrophils.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The differential leukocyte count showed that neutrophils are the principal target cells involved in the anti-in ammatory effect of AAL. Similar results have been observed in rats for the lectins isolated (Dalbergieae tribe) from Lonchocarpus sericeus [17,18] and L. araripensis [19], presenting binding a nity for N-acetylglucosamine. In addition, the interference of AAL in neutrophil migration was also con rmed by the reduced MPO activity in the paw, a heme-containing enzyme that is abundantly expressed in neutrophils.…”
Section: Discussionsupporting
confidence: 85%
“…Accordingly, the antiin ammatory effect of leguminous lectins is characterized by the preferential inhibition on cellular events of acute in ammation [21,29,30]. Other isolated lectins belonging to the Dalbergieae tribe also showed inhibitory effect on carrageenan-induced paw edema such as that of L. sericeus [17][18], L. araripensis [30] and L. campestris [19].…”
Section: Discussionmentioning
confidence: 99%
“…These proteins can modulate several processes like infection, cell recognition, cell communication, and various intracellular responses [14,15] . Plant lectins have shown anti‐inflammatory [16,17] and antinociceptive [18,19] effects. For example, some studies have proposed that lectins can modulate inflammation and pain through interactions of their carbohydrate‐binding domains with glycosylated selectin‐binding sites [20] or δ‐ and κ‐receptors, [21] respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The lectin isolated from Lonchocarpus araripensis (LAL), belonging to Dalbergieae tribe, recognizes and specifically binds to N-acetyl-D-glucosamin [2]. Several effects have already been evidenced for LAL, such as vasorelaxant [3], anti-inflammatory [2,4], and antinociceptive [5,6], also a protective effect on sepsis model [7]. In respect to the antinociceptive activity, LAL has a pleiotropic effect in several nociceptive pathways, being associated to the modulation of inflammatory and/or hypernociceptive mediators [5,6].…”
Section: Introductionmentioning
confidence: 99%